The Improvement of The Discipline for Early Childhood Through Token Economy Technique - Elizabeth Prima; Putu Indah Lestari (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2018)
This study aims to determine the improvement of the discipline for early childhood through Token Economy technique.  This study has been carried out on the Group A students of Kindergarten of Kumara Asri Denpasar academic year 2017/2018. This type of research is Classroom Action Research using observational method.  The subject of this class action research is 26 students of group A Kindergarten of Kumara Asri; consist of 14 girls and 12 boys.  The object of this study is the application of Token Economy technique to improve the discipline of early child. The results obtained in First Cycle showed that 17 students (65.38%) had achieved learning completeness, whereas in Second Cycle, 24 students (92, 31%) have reached learning mastery. There is a 26.93% increase in child discipline with the application of Token Economy technique from first to second cycle. This means that the application of Token Economy technique can improve the discipline of early childhood